Convergence of Solutions of Certain Fourth-Order Nonlinear Differential Equations - B. S. Ogundare (International Journal of Mathematics and Mathematical Sciences, 2007)
We give sufficient criteria for the existence of convergence of solutions for a certain class of fourth-order nonlinear differential equations using Lyapunov's second method. A complete Lyapunov function is employed in this work which makes the results to include and improve some existing results in literature.